Zoro and the guardians of Chiribiquete : the design of creatures for VR location-based experience to contribute to the preservation of Chiribiquete National Park : a thesis presented in partial fulfilment of the requirements for a Master in Design, Weta Workshop School at Massey University, Wellington, New Zealand - Fernández Zapata, Sara Isabel (Massey University, 2024)
Fantasy worlds, creatures, and their stories can inspire people to learn and care about specific places, creating empathy and a sense of identity that transcends differences between cultures. “Chiribiquete” is a Colombian national park that only researchers and indigenous communities, to whom this place is sacred, should visit. This park, one of the world’s largest tropical rainforest national parks, belongs to Unesco’s World Heritage Sites List. Due to the park’s fragile biomass and its sacred significance to several indigenous communities, visitation is strictly limited. Therefore, location-based VR experiences can help to create a sense of belonging around this place. My design outcome consists of three creatures for a VR Location-Based Experience in the Gold Museum of Bogotá, based on the fantasy book Zoro by Jairo Anibal Niño. Zoro is a fantasy story about an indigenous child looking for his people in the Amazonian rainforest. This book has been part of the Colombian education syllabus for over three decades, facilitating a connection between Colombian identity and the Amazon rainforests. This project aims to communicate the relevance of preserving Chiribiquete National Park by offering an alternative to allow teenagers to empathise with this sacred place remotely. Drawing on IDEO methodology, I have developed creatures for a VR experience based on Zoro combined with Chiribiquete’s cosmogony. Based on the creatures from the book, these designs employ fantasy to help people understand the park’s complexity and the need for its conservation.
Keywords: 330316 Visual communication design (incl. graphic design)